毛振翧的《苗疆集》研究 - Yang Ting; Fan Jia (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2025)
When Mao Zhenxuan, a Chinese poet in the Qing Dynasty, served in Guizhou, he left two volumes of the poetry collection of The Miao Jiang Collection. The study, using literature research and text analysis methods, aims to explore the content and historical value of the Miao Jiang Collection. The paper discusses Mao Zhenxuan's poetry creation during his tenure in Guizhou. This study focuses on the analysis of the creation theme, artistic characteristics and aesthetic paradigm of Miao Jiang Collection, and finally summarizes its historical value. The study shows that the poems of Miao Jiang Collection not only vividly depict the natural and precipitous and folk customs of Miao Jiang, but also recorded the military conflicts and cultural interactions in the border governance of the Qing Dynasty.Moreover, the spirit of self-annotation and factual recording in the poem enhances its value as a historical document. This study holds that Mao Zhenxuan's Miao Jiang Collection is not only a model of literary creation, but also an important historical material for the study of frontier policy and ethnic relations in the Qing Dynasty.